Observations on hematogones with light chain restriction. (2022) - D'Ardia, Angela; Ciliberti, Valeria; Zeppa, Pio; Caputo, Alessandro
Abstract: Light-chain restricted hematogones (LCR HGs) detected by flow cytometry (FC) may, occur in bone marrow mimicking involvement by a B-cell lymphoma. This phenomenon can present a diagnostic pitfall and negatively impact patient management, and may occur in other organs, including lymph nodes, For this reason, it is recommended to utilize, in case of LCR in lymph node, one additional morphological, phenotypical or molecular criteria for the diagnosis of lymphoma on cytological samples.